Versatile seamless DNA vector production in E. coli using enhanced phage lambda integrase. - Suki Roy; Sabrina Peter; Peter Dröge (PLoS ONE, 2022)
Seamless DNA vectors derived from bacterial plasmids are devoid of bacterial genetic elements and represent attractive alternatives for biomedical applications including DNA vaccines. Larger scale production of seamless vectors employs engineered Escherichia coli strains in order to enable tightly regulated expression of site-specific DNA recombinases which precisely delete unwanted sequences from bacterial plasmids. As a novel component of a developing lambda integrase genome editing platform, we describe here strain MG1655-ISC as a means to easily produce different scales of seamless vectors, ranging in size from a few hundred base pairs to more than ten kilo base pairs. Since we employed an engineered lambda integrase that is able to efficiently recombine pairs of DNA crossover sites that differ in sequence, the resulting seamless vectors will be useful for subsequent genome editing in higher eukaryotes to accommodate variations in target site sequences. Future inclusion of single cognate sites for other genome targeting systems could enable modularity. These features, together with the demonstrated simplicity of in vivo seamless vector production, add to their utility in the biomedical space.